(untitled) (International Current Pharmaceutical Journal, 2013)
The present study involves in the formulation and evaluation of sustained release tablets of Voriconazole (250mg). The objective of the present study was to formulate Voriconazole sustained release tablets by wet granulation method by using natural (Xanthan gum, Karaya gum) and semi synthetic polymers (HPMC K100M). Lactose was used as diluting agent, Magnesium stearate was used as a lubricant and Talc was used as a glident. These sustained release tablets can release the drug up to 12 hours in predetermined rate. The formulated powder blend was evaluated for bulk density, tapped density, compressibility index and angle of repose. The formulated tablets were evaluated for physical characteristics of sustained release tablets such as thickness, hardness, friability, weight variation and drug content. The results of the formulations found to be within the limits specified in official books. The tablets were evaluated for In-vitro drug release studies by using USP type I dissolution test apparatus. The dissolution test was performed in 0.1 N HCL for 2 hr and phosphate buffer pH 6.8 for 10hrs. The in-vitro cumulative drug release profile of all formulations F1-F10 at 12 hours showed 84.25% to 99.82% drug release, respectively. From the data it was clear that by increasing the amount of polymer in the formulation the amount of drug release was decreased. Hence, Formulation F9 was the most promising formulation as it gives satisfactory release (99.82%) for 12 hours and F9 found to be the best formulation. DOI: http://dx.doi.org/10.3329/icpj.v2i10.16410 International Current Pharmaceutical Journal, September 2013, 2(10): 165-169